The McGraw-Hill handbook of business letters - Poe, Roy W. (McGraw-Hill, 1994)
Includes everything you need to know to write clear, concise, effective letters for any business situation. Whether you're creating an in-house memo for your fellow co-workers or specialized correspondence for customers and clients, this all-in-one guide will show you the proper style, format, and type to use in all your professional communications. With this comprehensive resource, you can easily access hundreds of sample letters for a wide range of business applications. You can find exactly the right words for the right job and strike a perfect balance between formal and casual styles. Best of all, you can communicate with confidence--and go "write" to the top--in business and in life.